2022
DOI: 10.1101/2022.07.06.498921
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Faecal virome of the Australian grey-headed flying fox from urban/suburban environments contains novel coronaviruses, retroviruses and sapoviruses

Abstract: Bats are important reservoirs for viruses of public health and veterinary concern. Virus studies in Australian bats usually target the families Paramyxoviridae, Coronaviridae and Rhabdoviridae, with little known about their overall virome composition. We used metatranscriptomic sequencing to characterise the faecal virome of grey-headed flying foxes from three colonies in urban/suburban locations from two Australian states. We identified viruses from three mammalian-infecting (Coronaviridae, Caliciviridae, Ret… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 72 publications
0
2
1
Order By: Relevance
“…CC-BY 4.0 International license perpetuity. It is made available under a preprint (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in The copyright holder for this this version posted October 21, 2022. ; https://doi.org/10.1101/2022.10.20.513122 doi: bioRxiv preprint associated with the diet (26). Notably, no mammalian viruses belonging to the Flaviviridae, as well as only one short contig matching to Astroviridae and two short contigs matching to Picornaviridae, where identified in marked contrast to the results presented here (26).…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…CC-BY 4.0 International license perpetuity. It is made available under a preprint (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in The copyright holder for this this version posted October 21, 2022. ; https://doi.org/10.1101/2022.10.20.513122 doi: bioRxiv preprint associated with the diet (26). Notably, no mammalian viruses belonging to the Flaviviridae, as well as only one short contig matching to Astroviridae and two short contigs matching to Picornaviridae, where identified in marked contrast to the results presented here (26).…”
Section: Discussioncontrasting
confidence: 64%
“…Although characterising the faecal virome of bats is important for identifying novel and potentially zoonotic viruses, especially from urban bat populations, the identification of dietary invertebrate and plant viruses is common, such that viromes may differ between faecal and tissue samples (23)(24)(25). Our previous study of the faecal virome of the grey-headed flying fox identified bat viruses belonging to the Coronaviridae and Caliciviridae, as well as a myriad of insect and plant viruses likely associated with the diet (26). Notably, no mammalian viruses belonging to the Flaviviridae, as well as only one short contig matching to Astroviridae and two short contigs matching to Picornaviridae, where identified in marked contrast to the results presented here (26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation